In vitro fertilization program in white rhinoceros - Hildebrandt, Thomas Bernd; Holtze, Susanne; Colleoni, Silvia; Hermes, Robert; Stejskal, Jan; Lekolool, Isaac; Ndeereh, David; Omondi, Patrick; Kariuki, Linus; Mijele, Domnic; Mutisya, Samuel; Ngulu, Stephen; et al. (Reproduction (Cambridge, England), 2023)
IN BRIEF: To save endangered rhinoceros species, assisted reproductive technologies are warranted. We here report in vitro blastocyst generation of the Near-Threatened Southern white rhinoceros and, for the first time, also of the technically Extinct Northern white rhinoceros. ABSTRACT: The Anthropocene is marked by a dramatic biodiversity decline, particularly affecting the family Rhinocerotidae. Three of five extant species are listed as Critically Endangered (Sumatran, Javan, black rhinoceros), one as Vulnerable (Indian rhinoceros), and only one white rhino (WR) subspecies, the Southern white rhinoceros (SWR), after more than a century of successful protection is currently classified as Near Threatened by the IUCN, while numbers again are declining. Conversely, in 2008, the SWR's northern counterpart and second WR subspecies, the Northern white rhinoceros (NWR), was declared extinct in the wild. Safeguarding these vanishing keystone species urgently requires new reproductive strategies. We here assess one such strategy, the novel in vitro fertilization program in SWR and - for the first-time NWR - regarding health effects, donor-related, and procedural factors. Over the past 8 years, we performed 65 procedures in 22 white rhinoceros females (20 SWR and 2 NWR) comprising hormonal ovarian stimulation, ovum pick-up (OPU), in vitro oocyte maturation, fertilization, embryo culture, and blastocyst cryopreservation, at an efficiency of 1.0 ± 1.3 blastocysts per OPU, generating 22 NWR, 19 SWR and 10 SWR/NWR hybrid blastocysts for the future generation of live offspring.
Keywords: indukce ovulace; Ovulation Induction; zvířata; ženské pohlaví; Fertilization in Vitro; Reproductive Techniques, Assisted; fertilizace in vitro; asistovaná reprodukce; Female; Animals; Blastocyst; Perissodactyla; blastocysta